Decision Support System for Toddler Vaccination Coverage at Bunga Teratai Posyandu, Lokon Hamlet, Using the SMART Method - Muhammad Azmi; Fitriani Fitriani (PT. GWEX NET PUBLISHER, 2026)
Posyandu (Integrated Healthcare Center) is a primary health facility that plays a vital role in monitoring growth and providing immunizations for toddlers. However, at the Bunga Teratai Posyandu in Lokon Hamlet, the decision-making process regarding toddler vaccination coverage is still conducted manually and remains suboptimal. This can lead to inaccuracies in vaccination prioritization and data collection. This study aims to develop a Decision Support System (DSS) to assist Posyandu cadres and health officers in determining toddler vaccination coverage more quickly and accurately. The method used in this system is SMART (Simple Multi-Attribute Rating Technique), which operates by assigning weights to predefined criteria, such as the toddler's age, body temperature, and vaccine type. The system is designed to process data structurally and provide recommendations based on the highest calculated values. The results of this study indicate that the SMART method can effectively rank vaccination priorities, thereby facilitating more efficient data management and decision-making for health officers at Bunga Teratai Posyandu.